COGNIÇÃO SOCIAL E INTELIGÊNCIA ARTIFICIAL NA LINGUÍSTICA JURÍDICA (Reflection and Critique Law Magazine, 2026)
ABSTRACT: this paper proposes an interdisciplinary analysis of social cognition, artificial intelligence (AI), and linguistic studies, with a particular focus on the legal field. To this end, it explores the concept of social cognition, emphasizing its relevance in the processes of language interpretation and production, as well as its application within linguistic studies—especially in legal discourse. The article also addresses cognition from the perspective of neurolinguistics, highlighting how mental and linguistic processes interact in the comprehension and formulation of legal texts. Furthermore, it examines the integration of artificial intelligence into legal practices, critically assessing its impacts on social cognition, particularly from an ethical and technical standpoint. This includes the risk of perpetuating algorithmic biases, which may influence public opinion and judicial decisions.Keywords: cognition; linguistics; AI.